Does Trade Openess and Transportation Intensity Promote Enviromental Degradation in Indonesia? - Mochammad Yusuf; Difa Riza Fahlefi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
Transportation is one of the most important sectors in supporting all economic activities in order to support inclusive economic development. However, in its development, trade openness triggers high economic activity that triggers environmental pollution, one of which is the impact of the transportation sector. This study aims to estimate the effect of trade openness and transportation intensity as well as total factor productivity as a proxy for technological development on the growth of carbon emissions in Indonesia. The methods used in this research are Engle-Granger ECM and Granger Causality. The results show that in the long-term trade openness and transportation intensity have a significant positive effect, while the total productivity factor has a significant negative effect. In the short term with the same direction of influence, total productivity factors and transportation intensity have a significant effect, but trade openness does not have a significant effect. Furthermore, there is a unidirectional effect of fossil energy consumption on transportation intensity & trade oponess on transportation intensity. Last, transportation intensity and trade openness have been shown to have a bidirectional relationship.